Sedation and renal impairment in critically ill patients: a post hoc analysis of a randomized trial - Strøm, Thomas (BioMed Central, 2011)
INTRODUCTION: Not sedating critically ill patients reduces the time patients receive mechanical ventilation, decreases the time in the intensive care department and reduces the total hospital length of stay. We hypothesized that no sedation improves hemodynamic stability, decreases the need for vasoactive drugs, diminishes the need for extra fluids and lowers the risk of acute kidney injury. METHODS: We performed an evaluation on the database from our previous trial of 140 patients randomized to either no sedation vs. sedation with a daily interruption of sedatives. A total of 113 patients were included in the previous statistical analysis. Ten patients had pre-existing renal impairments and were excluded. Data were collected from observational cards and blood samples. RESULTS: A total of 103 patients were included in this retrospective review. We registered an increased urine output in the group receiving no sedation compared to the sedated control group (1.15 ml/kg/hour (0.59 to 1.53) vs. 0.88 ml/kg/hour (0.052 to 1.26), P = 0.03). In addition we saw a decrease in the number of patients with renal impairment according to the RIFLE classification (indicating Risk of renal dysfunction; Injury to the kidney; Failure of kidney function, Loss of kidney function and End-stage kidney disease) in the group receiving no sedation compared to the sedated control group (25 (51%) vs. 41 (76%), P = 0.012). The difference in the two groups with respect to mean arterial blood pressure, fluid balance and use of vasoactive drugs was not significant. CONCLUSIONS: A no sedation strategy to patients undergoing mechanical ventilation increases the urine output and decreases the number of patients with renal impairments. TRIAL REGISTRATION: ClinicalTrials.gov registration number NCT00466492.